Achieving High Efficiency of PTB7‐Based Polymer Solar Cells via Integrated Optimization of Both Anode and Cathode Interlayers. Issue 8 (13th February 2014) - Gu, Cheng; Chen, Youchun; Zhang, Zhongbo; Xue, Shanfeng; Sun, Shuheng; Zhong, Chengmei; Zhang, Huanhuan; Lv, Ying; Li, Fenghong; Huang, Fei; Ma, Yuguang
<x xml:space="preserve">Abstract</x> A poly(thieno[3, 4‐b]‐thiophene/benzodithiophene) (PTB7)‐based polymer solar cell (PSC) with conventional structure can achieve a significant power conversion efficiency of 8.42%, which is realized by integrated optimization of both anode and cathode interlayers. The effects of a conjugated microporous polymer film as the anode interlayer are threefold: it enhances the contact with active layer, increases the work function and conductivity, and blocks electrons. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>